Design of two stroke SI linear engine with spring mechanism - Mohd Faizal, Mohd Pauzi (2008)
The objectives of this research project is to design the spring mechanism of single cylinder two stroke SI linear engine, to analyze the stress of spring mechanism of linear engine and draw the single cylinder two stroke SI linear engine. The problem arise when the modern control technology that available today is expensive to be used with small linear engine and spring is proposed to solve the related problem of piston motion control for this project. The design of the linear engine with spring mechanism for this project is based on conventional two-stroke engine. The modification is made for the crankcase, crankshaft, and connecting rod of conventional two-stroke engine with new crankcase, spring and new connecting rod of linear engine. The SI linear engine with spring mechanism is modeled by using Solid works software and the spring software is used to design the spring for this linear engine for this project.